The Trypomastigote Small Surface Antigen (TSSA) regulates Trypanosoma cruzi infectivity and differentiation. - María de Los Milagros Cámara; Gaspar E Cánepa; Andrés B Lantos; Virginia Balouz; Hai Yu; Xi Chen; Oscar Campetella; Juan Mucci; Carlos A Buscaglia (Public Library of Science (PLoS), 2017)
TSSA (Trypomastigote Small Surface Antigen) is an antigenic, adhesion molecule displayed on the surface of Trypanosoma cruzi trypomastigotes. TSSA displays substantial sequence identity to members of the TcMUC gene family, which code for the trypomastigote mucins (tGPI-mucins). In addition, TSSA bears sequence polymorphisms among parasite strains; and two TSSA variants expressed as recombinant molecules (termed TSSA-CL and TSSA-Sy) were shown to exhibit contrasting features in their host cell binding and signaling properties.Here we used a variety of approaches to get insights into TSSA structure/function. We show that at variance with tGPI-mucins, which rely on their extensive O-glycoslylation to achieve their protective function, TSSA seems to be displayed on the trypomastigote coat as a hypo-glycosylated molecule. This has a functional correlate, as further deletion mapping experiments and cell binding assays indicated that exposition of at least two peptidic motifs is critical for the engagement of the 'adhesive' TSSA variant (TSSA-CL) with host cell surface receptor(s) prior to trypomastigote internalization. These motifs are not conserved in the 'non-adhesive' TSSA-Sy variant. We next developed transgenic lines over-expressing either TSSA variant in different parasite backgrounds. In strict accordance to recombinant protein binding data, trypomastigotes over-expressing TSSA-CL displayed improved adhesion and infectivity towards non-macrophagic cell lines as compared to those over-expressing TSSA-Sy or parental lines. These phenotypes could be specifically counteracted by exogenous addition of peptides spanning the TSSA-CL adhesion motifs. In addition, and irrespective of the TSSA variant, over-expression of this molecule leads to an enhanced trypomastigote-to-amastigote conversion, indicating a possible role of TSSA also in parasite differentiation.In this study we provided novel evidence indicating that TSSA plays an important role not only on the infectivity and differentiation of T. cruzi trypomastigotes but also on the phenotypic variability displayed by parasite strains.